PEMETAAN SEBARAN PRASARANA DAN BATAS DESA TELUK BATANG KECAMATAN TELUK BATANG KABUPATEN KAYONG UTARA - Robin Saputra; Adityo Raynaldo; Sofi Siti Shofiyah; Etha Marista; Zan zibar; Riza Linda (Jurnal Pengabdian Agro and Marine Industry, 2022)
Village boundaries are the boundaries of government administration areas between one village and another. Village administrative boundaries become very important along with the advancement of regional development and growth in the region. The purpose of this PKM activity is the availability of village boundary maps in printed form to support village governments in carrying out government functions, planning and policies. Making village maps involves the village and surrounding communities. The results of this village mapping activity can be carried out and completed properly. The results of the evaluation of activities, the resulting map is representative for the needs of village administration. The village government was very happy and stated that this activity was very useful and in the future there will be further activities, with the output targets of hamlet boundary maps, land use and road names.